The Interactional Effect of Gender with Emotionally Focused Couple Therapy on Marital Burnout in Counseling Centers of Tehran - Fariba Ebrahimi-Tazekand; Parivash Vakili; Farideh Dokaneifard (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Marital burnout is a gradual reduction of affection to the spouse, which is associated with alienation, unwillingness and indifference of couples to each other and the replacement of negative emotions rather than positive emotions. The aim of this study was to evaluate the interactional effects of gender with Emotionally Focused Couple Therapy (EFCT) on couple burnout in counseling centers of Tehran. Materials and Methods: This study was semi-experimental with pre-Test, Post-Test, Follow-up design and control group. The study population included all couples who were referred to counseling centers due to marital conflicts. Among the study population, 30 couples who had a standard deviation above the average of burnout questionnaire, were selected purposeful sampling method, and randomly divided into two groups of experimnental and contorl. The experimental group received 10 sessions EFCT once a week. Data were collected via Marital Burnout Measurment. Covariance and Repeated measures analysis were used for data analysis in SPSS-22. Results: The mean (SD) age of the experimental group was 32.4 (3.2) and 34.2 (4.1) years for the control group. EFCT reduced the marital burnout and its components, as the mean somatic burnout score in the experimental group vireid form 31.6 (4.1) to 25 (3.3), P<0.001; emotional burnout from 35 (4.8) to 26.3 (3.8), P<0.001; and psychological burnout from 33.4 (4.8) to 31.4 (5.2), P<0.001; and marital burnout from 100 (9.1) to 76.8 (8.1), P<0.001. There was no significant effect of gender on marital burnout in both groups. Conclusion: The study showed that the emotionally focused couple therapy was effective in decreasing marital burnout; however, gender showed no significant interactive effect on emotionally focused couple therapy. DOI: http://doi.org/10.22037/ch.v5i4.19338